Blogging during the Pandemic: An Action Research - Karthika, J.; N, Akshaya (Indian Journal of Educational Technology, 2025)
The paper focuses on the advantages of using a class blog to improve the writing skills of postgraduate literature students. The pandemic enabled all the learners to use technology uniformly, and therefore, it was possible to use a class blog to improve the writing skills of the learners. An action research was planned and conducted to improve the engagement level of the postgraduate students during the pandemic and also to enhance their writing skills as well. Feedback was collected at the end of the semester to gauge the impact of using blogs in the classroom. The usage data retrieved from the class blog has also been analyzed quantitatively to measure the engagement level of the learners. Both the quantitative and the qualitative data obtained at the end of the semester show improvement in the engagement level of the learners. The writing skills of a few of the learners showed considerable improvement. The action research revealed that the opportunity provided boosted the confidence of the majority of the learners in the classroom in expressing their thoughts in writing. The reflection of the teacher and learners revealed the positive impact of feedback on the entire writing process.